المسائل الفقهية التي حكى فيها ابن رشد الإجماع في كتابه بداية المجتهد ونهاية المقتصد جمعا ود ا رسة كتاب النكاح أنم وذجا - بن عمي, إسماعيل (University of Eloued-جامعة الوادي, 2014)
Our task is divided into two parts:theoritical and practical; the first one consists of the translation of Ibn Rochd and the redefinition of his book " Bidayet El Moujtahid" and his method in formulating; furthermore, it consists of a theoritical study of about " Idjmaa" unanimity in adition of collecting and studing " Massail Fikhiaa" in which he mentionned " Idjmaa" chater of "Nikah" marriage in the book of " Bidayet El Moujtahid wa Nihayet Almoktasid" looking for the question is it ready for to be discussion and if it exposed to different points of view. Mentionning the reference of this unanimity "Idjmaa "treats the "idjmaa" closely besides the " Idjmaa" and "ittifak" (unanimity and conicidence ) are a like in adition that " Idjmaa" is not knowing the opposit
مذكرة ماستر
Keywords: المسائل الفقهية- بن رشد - الاجماع -النكاح; Jurisprudence issues - Ibn Rushd - consensus - marriage